Rumen ciliates of domestic cattle (Bos taurus taurus) in Kastamonu, Turkey, with the description of a new species - Gürelli, Gözde (Elsevier BV, 2016)
Species composition and distribution of ciliates were investigated in the rumen contents of 25 domestic cattle (Bos taurus taurus L.) living in Kastamonu, Turkey. Forty-seven species and 37 morphotypes representing 15 genera were identified. Of them, a new species of Ostracodinium was recognized and described as Ostracodinium anatolicum n. sp. This new species has two caudal lobes. The dorsal lobe is small and rounded and the ventral lobe is triangular shaped and bent toward the dorsal side like a thick hook. Furthermore, the anterior end of the macronucleus (1/5 of the length) is bent toward the left like a hook. The density of rumen ciliates in cattle was 96.8±43.3×104cellsmL-1 and the mean number of ciliate species per host was 14.2±4.4. Entodinium longinucleatum, E. nanellum, E. simulans and Isotricha prostoma were the most abundant species, each with a prevalence of 88%. Entodinium chatterjeei, E. bifidum m. monospinosum, Hsiungia triciliata, Oligoisotricha bubali, Ostracodinium dogieli, O. mammosum and O. munham are new host records for cattle from Turkey.
Keywords: Rumen; Species Specificity; Turkey; Animals; Cattle; Biodiversity; Ciliophora; 2. Zero hunger